Percepção do uso da tecnologia de informação no agronegócio: um estudo de caso na Cooperativa Regional dos Suinocultores de Passos-MG - Silva, Cristiane Rocha (2005)
The objective of this dissertation was to analyze the process of information technolgy (IT) use in agribusiness, focusing the perception of the directors, employees and pork producers related to the Regional Cooperative of Pork Producers ofPassos (Coperpassos). The data was colected based on the qualitative and quantitative aproach, using questionnaires, observation, field notes and semi-structured interviews. Among the subjects that were interviewed were directors, employees, managers, technicians and associate businessmen related to the Coperpassos. We noticed that the decision ofusing IT is related to the managing atitude ofthe rural businessman front to the activity. The results showed that the businessmen who use IT, those who are potential users and those who are resistam present different managment profiles. The chapter refering to data description, analysis and interpretation ofthe collected data presents first the pork producing chain in Passos. It emphasysis the criticai factors mentioned by the interviewed subjects: the imput supply and consumer markets and the handiwork qualification. Then, we describe the software used by the cooperative (Copersis) and the profile ofthe pork producer member ofthe cooperative based on the questionnaires and declarations in the interviews. Another aspect that was evaluated was the use ofinformation technology and the perceptions ofadvantages and barriers to its use from the point ofview ofpork producers who use IT and those who do not use IT, and also from the point of view ofthe cooperative employees. There was a similarity between the theoretic fundaments and the empiric results related to the impact of IT in organizations. Different actors identified the cooperative as a form of diffusing technology. This work presents the necessity of managing profissionalization, aknowledgement ofthe value ofinformation and the benefits ofcontrol toois as pre-conditions for the effective use of informatization, therefor contributing for the difusion of IT. On the other nanei, it pojnts out the necessity of a software development model that meets the managment necessities ofthe users.